The Impact of Auditor Selection on Financial Statement Quality: Evidence from Listed Companies in Indonesia - Dewi, Sari; Wati, Lidia; Karjantoro, Handoko; Harsono, Budi (Dinasti Publisher, 2025)
This study aims to analyze the impact of auditor selection on the quality of financial statements by considering factors such as auditor independence, competence, and reputation as key determinants of transparency and accountability in financial reporting. Using a quantitative approach with descriptive and causal-comparative methods, the study analyzes secondary data from companies listed on the Indonesia Stock Exchange (IDX). The sample was selected through purposive sampling based on criteria such as completeness of financial reports and the presence of audited statements. The results reveal that auditor selection whether from Big Four or non-Big Four firms does not significantly affect the quality of financial statements. Instead, total accruals show a significant negative effect, indicating that internal financial practices play a more substantial role than auditor type in determining financial reporting quality. Despite this, prior literature emphasizes that auditor quality, industry specialization, and experience still contribute indirectly by strengthening oversight. Therefore, future research should explore additional variables such as auditor tenure, audit committee effectiveness, and corporate governance as mediators or moderators. Expanding the sample and observation period, as well as applying multi-dimensional measures of financial statement quality, such as earnings persistence and conservatism, can improve the robustness and generalizability of findings.